Prevalence of anemia and its relationship with neurological status in patients undergoing surgery for degenerative cervical myelopathy and radiculopathy: A retrospective study of 2 spine centers. (February 2020) - Nouri, Aria; Matur, Abhijith; Pennington, Zach; Elson, Nora; Karim Ahmed, A.; Huq, Sakibul; Patel, Kishan; Jeong, William; Nasser, Rani; Tessitore, Enrico; Sciubba, Daniel M.; Cheng, Joseph S.
Highlights: Anemia is associated with poorer baseline neurological status. In myelopathic patients, macrocytic anemia associated with pre-operative Nurick grade. Anemia and myelopathy commonly co-occur in elderly patients. Abstract: Both degenerative cervical myelopathy (DCM) and anemia are common among older patients, however insufficient data exists evaluating their co-occurrence and the influence of anemia on baseline neurological status. To address this, we examined a retrospective multicenter series of patients treated for DCM or radiculopathy. Myelopathy was graded using the Nurick scale. Established criteria for diagnosing abnormalities were used to identify blood abnormalities, including macrocytic and microcytic anemia. Multivariable regression was used to determine the impact of hematological anomalies on Nurick grades. In our analysis, we included 725 patients (age of 57.1 ± 11.7), of whom 398 presented with myelopathy and 327 presented with radiculopathy alone. Twenty six percent of all patients were anemic at baseline and the mean preoperative Nurick grade across all patients was 2.09 ± 1.29; mean Nurick grade amongst those with DCM was 2.98 ± 1.12. Compared to those with myelopathy, patients with radiculopathy were significantly younger (53.8 ± 11.0 vs 59.8 ± 11.6, p < 0.001) and less likely to be anemic (16.8% vs 33.7%, p < 0.0001). Nurick grading was significantly higher in myelopathy patients with anemia (3.13 ± 1.19 vs 2.91 ± 1.07, p = 0.05) and macrocytic anemia (4.00 ± 1.41 vs 2.97 ± 1.11, p = 0.04). Multivariate regression demonstrated that anemia (p < 0.001), age (p < 0.0001), and posterior surgical approach (p < 0.0001) were related to worse preoperative Nurick grade. In sum, these data suggest that anemia and degenerative cervical spine pathologies commonly co-occur. Anemia, and macrocytic anemia specifically, is associated with poorer neurological status in myelopathic patients. These data suggest anemia may influence baseline neurological status and impact surgical recovery in patients treated for DCM or radiculopathy.